2021
DOI: 10.1177/10731911211036760
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Posttrauma Risky Behaviors Questionnaire: Item Response Theory Analyses

Abstract: The Posttrauma Risky Behaviors Questionnaire (PRBQ) assesses extent of engagement in posttrauma reckless and self-destructive behaviors (RSDBs). Given PRBQ’s recent development with limited psychometric investigations, we used item response theory to examine (a) item analysis, (b) person fit, and (c) differential item functioning (DIF) across gender-based groups and two different samples. One sample included 464 participants reporting potentially traumatic experiences (Mechanical Turk [MTurk], recruited online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 107 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…For the specific analyses examining the number of delinquent behaviors, we excluded the PRBQ Item 7 examining illegal behaviors due to its overlap with the delinquency construct when computing the total PRBQ score. The PRBQ scores have good psychometrics (Contractor et al, 2020, 2021; Natesan Batley et al, 2022), and in the current study, the Cronbach’s α was .78 for the total score, which excluded Item 7.…”
Section: Methodsmentioning
confidence: 50%
“…For the specific analyses examining the number of delinquent behaviors, we excluded the PRBQ Item 7 examining illegal behaviors due to its overlap with the delinquency construct when computing the total PRBQ score. The PRBQ scores have good psychometrics (Contractor et al, 2020, 2021; Natesan Batley et al, 2022), and in the current study, the Cronbach’s α was .78 for the total score, which excluded Item 7.…”
Section: Methodsmentioning
confidence: 50%
“…Recently, IRT was more and more applied to assess and revise the scales in public health or clinical studies (43). Different from the previous simplified studies just focused on the difficulty and discrimination when using IRT model (31,(62)(63)(64), our findings also integrated the equivalence and information of items into the criteria of remaining items in order to obtain a relative accuracy of measurement of health literacy for older adults. The previous study by Shen et al reported the overall reliability of original version was 0.95 among the population aged 15-69 years old in China (16).…”
Section: Discussionmentioning
confidence: 99%
“…Where was the response to item in the scale; was the discrimination parameter; was the difficulty parameter, which indicated the point where an individual would have a 50% chance of endorsing item ; and is the ability value being measured. The basic assumptions of IRT included unidimensionality, local independence, and monotonicity ( 25 29 ), which were assessed, respectively, by the eigenvalue examination in factor analysis ( 30 ), Yen’s Q3 statistic ( 29 ), splines modeling via flexible IRT models and Pearson χ 2 statistics ( 31 ) in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A knowledge-check item is one that asks for information that would only be known by a member of a target population (e.g., specific military information for a veteran-specific sample) (Weiss et al, 2021). This approach has been used to identify potential fraudulent responses as well as those who are inattentive (Natesan Batley et al, 2021;Shapiro et al, 2013;van Stolk-Cooke et al, 2018). This method also has limitations.…”
Section: Introductionmentioning
confidence: 99%